The ephemerality and micro-historicity of the postcolonial-urban: a critical case study of Asia’s urban mobility - Lin, Francis Chia Hui (Journal of Asian architecture and building engineering, 2025)
A global trend indicates a significant decline in physical activity, with more people opting to drive, often due to genuine or perceived safety concerns about other modes of transport or as a display of social status. I argue that this reflects the contemporary historicity of urban mobility, which has become a ubiquitous yet contested aspect of daily life, shaped by the Anthropocene. In Taiwan, stronger interpersonal and intergenerational trust fosters safer environments for active mobility. I propose that this arises from frequent cultural-political exchanges, reflecting the geopolitical context of Asia, where Western influences of modernisation and urbanisation play a significant role. In Taiwan, practices encouraging informal relationships amongst commuting stakeholders promote the flexible use of public spaces, which suggests features of ephemerality and micro-historicity. This study theorises urban mobility alongside these characteristics, rooted in Asia’s postcoloniality as reflected in its architectural and urban contexts. Methodologically, it maps key aspects of urban mobility and situates them within the historicity of the Asian built environment, challenging Western-dominated intellectual frameworks. The research critically explores Asia’s subalternity in urban settings, focusing on the removal of the Heping-Hsinsheng Pedestrian Overpass in Taipei to consolidate the concept of postcolonial-urban historicity.